Cancer management with Chinese medicine - Yu, Rencun; Hai, Hong (World Scientific, 2012)
"Significant advances made by Western medicine in the treatment of cancer are well-documented, but little has been written in English on complementary holistic treatment with Chinese medical methods that manage its symptoms and ameliorate the side effects of surgery, chemotherapy or radiotherapy. This book explains the complementary approach using cases from the medical files of Professor Rencun Yu, who was trained in Western medical oncology but also practices Chinese medicine. In addition, introductory chapters explain the basic principles of Chinese medicine, while other chapters."-- Resumé vydavatele
Keywords: čínské lékařství; maligní nádorová onemocnění; terapie; boj proti rakovině; Chinese medicine; cancer; therapy; cancer control; monografie; elektronické knihy; monographs; electronic books